Copper Dimer Anchored in g‐CN Monolayer as an Efficient Electrocatalyst for CO2 Reduction Reaction: A Computational Study. Issue 12 (9th November 2020) - Wang, Cong; Zhu, Changyan; Zhang, Min; Geng, Yun; Su, Zhongmin
Abstract: Electrocatalytic CO2 reduction (CO2 RR) into value‐added energy carriers is of utmost importance due to rising emissions of CO2 and depleting energy resource. The search and design of effective, stable, and low‐cost electrocatalysts are crucial but face huge challenges. Here, the potential of copper dimer anchored in g‐CN (Cu2 @CN) monolayer as electrocatalyst for CO2 RR is systematically evaluated by means of density functional theory calculations. The computational results indicate that the Cu2 @CN monolayer possesses superior catalytic activity for the conversion of CO2 to HCOOH and C2 H4 with low limiting potential (−0.16 and −0.52 V, respectively), outperforming the corresponding single‐atom counterpart (Cu@CN). Considering the myriad of unexplored dimers anchored in/on g‐CN monolayer and their potential catalytic applications, this work provides a useful guidance for future studies. Abstract : Copper dimer anchored in g‐CN monolayer exhibits excellent electrocatalytic activity for CO2 reduction to HCOOH and C2 H4 with low limiting potential (−0.16 and −0.52 V, respectively), outperforming a corresponding single‐atom counterpart.